Digital culture for Educational Organizations. Guidelines for Teachers and Education Agencies. - Cannizzo, Donatella (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Digital culture for Educational Organisations. Guidelines for Teachers and Education Agencies (Capogna et. al., 2020) was published in the post-emergency period of the Covid-19 pandemic in which the function performed by technological resources testifies to the extraordinary formative and relational capacities of digital media: the acquisition and exploitation of elaborated competences constitute the real key to access the e-learning system 5.0.